Quantifying priorities in business cycle reports: Analysis of recurring textual patterns around peaks and troughs - Alexander Foltas (Humboldt University Berlin, 2023)
I propose a novel approach to uncover business cycle reports' priorities and relate them to economic fluctuations. To this end, I leverage quantitative business-cycle forecasts published by leading German economic research institutes since 1970 to estimate the proportions of latent topics in associated business cycle reports. I then employ a supervised approach to aggregate topics with similar themes, thus revealing the proportions of broader macroeconomic subjects. I obtain measures of forecasters' subject priorities by extracting the subject proportions' cyclic components. Correlating these priorities with key macroeconomic variables reveals consistent priority patterns throughout economic peaks and troughs. The forecasters prioritize inflation-related matters over recession-related considerations around peaks. This finding suggests that forecasters underestimate growth and overestimate inflation risks during contractive monetary policies, which might explain their failure to predict recessions. Around troughs, forecasters prioritize investment matters, potentially suggesting a better understanding of macroeconomic developments during those periods compared to peaks.
urn:nbn:de:kobv:11-110-18452/27707-9
Keywords: E32; E37; C45; 330; Macroeconomic forecasting; Evaluating forecasts; Business cycles; Recession forecasting; Topic Modeling; Natural language processing; Machine learning; Judgemental forecasting